ANALYSIS OF OGAHIY'S GHAZALS AND THEIR ROLE IN THE MORAL EDUCATION OF STUDENTS - Barno Sapayeva Jumaboyeva (International Journal of Literature and Language Studies, 2026)
This study examines the thematic, artistic, and educational characteristics of Muhammad Rizo Ogahiy's ghazals and evaluates their role in the moral education of students. Employing a qualitative research design, the study applies descriptive, content, thematic, comparative, and interpretative analysis to selected ghazals from Ogahiy's Devon. The research explores how the poet conveys universal values such as honesty, justice, compassion, patriotism, humility, and the pursuit of knowledge through rich poetic imagery and philosophical reflection. The findings reveal that Ogahiy's ghazals possess significant pedagogical potential by fostering ethical awareness, critical thinking, cultural identity, and emotional intelligence among students. The study further demonstrates that integrating Ogahiy's literary heritage into literature education can strengthen value-based learning and contribute to the holistic development of learners. Moreover, the analysis confirms that the educational messages embedded in Ogahiy's poetry remain relevant to contemporary educational objectives and support the formation of morally responsible and culturally conscious individuals. The study concludes that Ogahiy's ghazals should be more actively incorporated into modern educational curricula as an effective resource for character education and the preservation of national literary heritage.